Meningkatkan Minat dan Hasil Belajar Peserta Didik dengan Project Based Learning (PjBL) di SMK Negeri 2 Bojonegoro - Nina Cahya Dwi Sugiharto; Listyaningsih Listyaningsih; Totok Sujatmiko (Departement of Mathematics Education, 2023)
Pancasila education in Vocational High Schools is a normative subject in which students are more enthusiastic about productive subjects according to their majors. This can be proven by the disinterest and lack of interest of students in participating in Pancasila Education lessons in class. This research is a Classroom Action Research conducted in 2 cycles by taking the subject of students in class X TKJ 2 at SMK Negeri 2 Bojonegoro. There are 36 students in this class with 13 female students and 23 male students. This research aims to increase students' learning interest and learning outcomes by using Project Based Learning. The method used in this research is tests and observations on students. The results of the research conducted show that the interest and learning outcomes of students have increased. Based on the results of observations of cycle II, it was obtained an average learning interest of students 83.4% (increased 17.7% from cycle I 66.7%) and learning outcomes 88.9% (increased41,7% from cycle I 47.2 %). The conclusion from this study is that using the Project Based Learning learning model can increase students' interest and learning outcomes in the Pancasila Education subject in class X TKJ 2 SMK Negeri 2 Bojonegoro.